Technique and outcome of percutaneous endoscopic transgastric jejunostomy for continuous infusion of levodopa-carbidopa intestinal gel for treatment of Parkinson's disease. (3rd June 2019) - Ishibashi, Yuji; Shimo, Yasushi; Yube, Yukinori; Oka, Shinichi; Egawa, Hiroki; Kohira, Yoshinori; Kaji, Sanae; Kanda, Satoshi; Oyama, Genko; Hatano, Taku; Hattori, Nobutaka; Fukunaga, Tetsu
Abstract: Objective: A new method of drug delivery via the small bowel, continuous infusion of levodopa-carbidopa intestinal gel (LCIG), for patients with advanced Parkinson's disease (PD) has been developed and shown to improve patients' quality of life. Levodopa is infused directly and continuously into the proximal jejunum via a percutaneous endoscopic transgastric jejunostomy (PEG-J) tube that is connected to a portable infusion pump. The aim of this study was to evaluate the safety and outcomes of our PEG-J technique performed in advance of LCIG therapy in patients with advanced PD. Material and methods: We reviewed the cases of 37 patients who underwent PEG-J for LCIG therapy at our hospital between November 2016 and May 2018. Pull-through percutaneous endoscopic gastrostomy (PEG) and gastropexy were performed in all patients. The J-tube was inserted through the PEG tube and placed beyond the ligament of Treitz endoscopically under fluoroscopic guidance. After two weeks, the gastropexy sutures were removed. Results: PEG-J with placement of the tube beyond the ligament of Treitz was successful in all 37 patients. Median procedure time was 26.4 min. Median hospital stay after the procedure was 16 days. Median follow-up with the PEG-J tube in place was 11 months. There were five procedure-related complications (13.5%) and 13 device-related complications (35.1%). There was no death related to the procedure. Conclusions: Our PEG-J technique can be performed safely in patients with advanced PD, and favorable outcomes have been achieved to date.